The Role of Fasting LDL-C Levels in Their Non-fasting Reduction in Patients With Coronary Heart Disease - Lin, Qiuzhen; Fu, Yan; Zang, XueYan; Liu, Qiming; Liu, Ling (Frontiers in Cardiovascular Medicine, 2021)
The level of low-density lipoprotein cholesterol (LDL-C) decreases to a certain extent after daily meals; however, the influencing factor of this phenomenon has not been fully elucidated. This study included 447 patients with coronary heart disease (CHD). Serum levels of blood lipid parameters at 0, 2 and 4 hours (h) after a daily breakfast were monitored in all subjects. The levels of total cholesterol (TC) , LDL-C, high-density lipoprotein cholesterol (HDL-C) and non-HDL-C significantly decreased, while those of triglycerides (TG) and remnant cholesterol (RC) significantly increased from baseline to 4 h in both male and female patients (P < 0.05). Multiple linear regression analysis showed that fasting LDL-C level, the nonfasting change in RC level at 4 h and fasting TG level were significant predictors of the nonfasting change in LDL-C level at 4 h in patients with CHD, and fasting LDL-C level was the most significantly associated with the nonfasting change in LDL-C level. Patients with lower levels of fasting LDL-C had smaller nonfasting changes in LDL-C levels. When the fasting LDL-C level was < 1.4 mmol/L, both absolute reduction and percent reduction in LDL-C level at 4 h were almost zero, which means that the nonfasting LDL-C level at 4 h was approximately equivalent to its fasting value (P < 0.05). This result indicated that the nonfasting changes in LDL-C levels were influenced by fasting LDL-C levels in patients with CHD. When the fasting LDL-C level was < 1.4 mmol/L, the nonfasting LDL-C level could replace the fasting value to guide treatment.